2006
DOI: 10.1016/j.febslet.2006.07.063
|View full text |Cite
|
Sign up to set email alerts
|

NMR studies of the fifth transmembrane segment of Na+,K+‐ATPase reveals a non‐helical ion‐binding region

Abstract: The structure of a synthetic peptide corresponding to the fifth membrane-spanning segment (M5) in Na + ,K + -ATPase in sodium dodecyl sulfate (SDS) micelles was determined using liquid-state nuclear magnetic resonance (NMR) spectroscopy. The spectra reveal that this peptide is substantially less a-helical than the corresponding M5 peptide of Ca 2+ -ATPase. A well-defined a-helix is shown in the C-terminal half of the peptide. Apart from a short helical stretch at the N-terminus, the N-terminal half contains a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…High-resolution structures of the R subunit nucleotide binding domain (15,16) and of its fifth transmembrane helix (17) have been determined by NMR or X-ray crystallography, and the structure of the Na,K-ATPase complex has been determined at 9.5 Å resolution by cryo-electron microscopy analysis of two-dimensional crystals of native kidney membranes (18). In this structure, the electron density map clearly identifies the arrangement of the 10 transmembrane helices of the R subunit as well as distinct regions assigned to the transmembrane domains of the and FXYD subunits.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…High-resolution structures of the R subunit nucleotide binding domain (15,16) and of its fifth transmembrane helix (17) have been determined by NMR or X-ray crystallography, and the structure of the Na,K-ATPase complex has been determined at 9.5 Å resolution by cryo-electron microscopy analysis of two-dimensional crystals of native kidney membranes (18). In this structure, the electron density map clearly identifies the arrangement of the 10 transmembrane helices of the R subunit as well as distinct regions assigned to the transmembrane domains of the and FXYD subunits.…”
mentioning
confidence: 99%
“…phospholipid bilayers (13,14); however, the direct formation of ion channels has not been demonstrated in ViVo, and recent evidence indicates that the role of FXYD proteins in ion transport regulation is solely related to their association with the Na,K-ATPase and other ion transporters. High-resolution structures of the R subunit nucleotide binding domain (15,16) and of its fifth transmembrane helix (17) have been determined by NMR or X-ray crystallography, and the structure of the Na,K-ATPase complex has been determined at 9.5 Å resolution by cryo-electron microscopy analysis of two-dimensional crystals of native kidney membranes (18). In this structure, the electron density map clearly identifies the arrangement of the 10 transmembrane helices of the R subunit as well as distinct regions assigned to the transmembrane domains of the β and FXYD subunits.…”
mentioning
confidence: 99%
“…The importance of helix M5 for the reaction mechanism of the Ca 2+ -ATPase and the N + /K + -ATPase has also been shown by spectroscopic studies. NMR studies revealed a flexibility of regions within the M5 segment that is necessary for ion binding and occlusion during the active transport [36,37]. Conformational changes of the Ca 2+ -ATPase upon calcium binding and release were monitored by infrared and fluorescence studies.…”
Section: Resultsmentioning
confidence: 99%
“…It is supposed that in these complexes the detergent micelle covers the hydrophobic region of the polypeptide, while possible hydrophilic termini are embedded in the water phase (Arora et al 2001). Several studies have shown that transmembrane polypeptides can retain and exhibit their natural conformation when solubilized in SDS solutions at concentrations well above the critical micelle concentration (cmc) (Arora et al 2001; Henry and Sykes 1994; Lazarova et al 2004; Papavoine et al 1994; Underhaug et al 2006). Due to its physicochemical characteristics, SDS is considered to be an ideal solubilizing detergent for hydrophobic membrane polypeptides; as in biological membranes, it has a negative net charge and can provide a good interface for the folding of surface-active peptides (Mammi and Peggion 1990).…”
Section: Introductionmentioning
confidence: 99%